(untitled) (Journal of Economic Research & Business Administration, 2024)
Indonesia is experiencing very rapid development, with a variety of modern payment systems that are widely used among the public. One of them is COD at Shopee.The rise in cases that occurred was caused by buyers misusing the COD system which resulted in several parties, namely couriers and sellers feeling disadvantaged, besides that the COD system at Shopee is a method that is easy, safe, and practical to use, about this problem raises various questions and the author’s goal is Islamic views on the use of COD on Shopee, the maqosid syariah perspective on COD. This type of research is field research, with qualitative methods producing descriptive data. Research results are Practice COD on Shopee contains practical, and efficient. This COD can be supported by maqoshid sharia because of the convenience in the mechanism which also reaches the Hujjiyat element if it is not implemented it difficulties and is included in the Hifdhu Mall. Key words: Shopee, Market, COD, Maqoshid sharia.